Laser-assisted lipolysis for arm contouring in Teimourian grades III and IV: A prospective study involving 22 patients. Issue 1 (March 2016) - Leclère, Franck Marie; Alcolea, Justo M; Vogt, Peter M; Moreno-Moraga, Javier; Casoli, Vincent; Mordon, Serge; Trelles, Mario A
Background: Upper arm deformities secondary to weight loss or senile elastosis have led to an increased demand for aesthetic contouring procedures. Objective: To objectively assess whether, in Teimourian high-grade upper arm remodelling, laser-assisted lypolysis (LAL) alone could result in patient satisfaction. Methods: Between 2012 and 2013, 22 patients were treated for excessive upper arm fat (Teimourian grade III and IV) solely with LAL. The laser used in the present study was a 1470 nm diode laser (Alma Lasers, Israel) with the following parameters: continuous mode, 15 W power and transmission through a 600 μm optical fibre. Previous mathematical modelling suggested that 0.1 kJ was required to destroy 1 mL of fat. Patients were asked to complete a satisfaction questionnaire. The arm circumference was measured pre- and postoperatively. Treatment parameters, adverse effects and outcomes were recorded. Results: Pain during the anesthesia and discomfort after the procedure were minimal. Complications included ecchymoses and prolonged edema. The mean (± SD) arm circumference decreased 5.5±1.0 cm in the right arm (P<0.01) and 5.2±1.1 cm in the left arm (P<0.01) in grade III patients and 4.9±1.1 cm in the right arm (P<0.01) and 4.9±1.1 cm in the left arm (P<0.01) in grade IV patients. Although the circumference of both arms significantly decreased in grade III and grade IV patients, the skin tightening remained incomplete. Overall, the average opinion of treatment was poor for both patients and investigators. Of the 22 patients, only nine (41%) would recommend this treatment. Conclusion: LAL for upper arm remodelling is not sufficient to ensure full skin tightening for patients with Teimourian grades III and IV upper arm deformities. A complementary surgery is mandatory for grades III and IV.